Diseño de concreto de alta resistencia fc=480 kg/cm usando agregados del río Huallaga para la ciudad de Tarapoto - García Torres, Mario (2013)
The problem we address in this research work, arises as need to use concrete high strength, for constructions in the city of arapoto. The lack of research on this subject, has motivated the author of this thesis to perform this work for the city of Tarapoto, which need this research for the design of special constructions, providing greater functionality and economy in comparison to conventional concrete. Then with certainty we can say that from this research will be used concrete high strength to improved designs in concrete for special constructions. The work has been investigated to design and get a concrete high strength f'c = 480 kg/cm2, with concrete pattern and additives. We used aggregates of maximum sizes of 3/4 ", 1/2" and 3/8 "achieved the required strength, but with different proportions of cement and aggregates, the same tie...